A Novel Metrics Based Technique for Code Clone Detection (International Journal of Engineering and Computer Science, 2018)
Nowadays, software development is a tricky and time-consuming task. In order to make the development easy, one uses the existing modules with or without little bit change. Modules which are used with or without change are called as code clones. In several places in case of same or different software, a clone can be used for development purpose. Without having care, copy and paste code can lead to inefficiency smell. This bad smell can be detected by finding and refactoring code clones. A clone can be detected by several existing techniques. In this paper, we present a metric based technique for code clone detection. The existing technique is able to detect method level clones only. We proposed the technique to detect module level clones using several metrics. Our technique is useful to find out type1 and type2 clones in software at modules level. For implementation purpose, we have developed a tool in Java named as JSCCD (JS Code Clone Detector) which can detect clones between Java files.